Sensory profiles of children born <30weeks' gestation at 2years of age and their environmental and biological predictors - Eeles, A.; Anderson, P.; Brown, N.; Lee, K.; Boyd, Roslyn; Spittle, A.; Doyle, L. (2013)
Background: Sensory profiles are increasingly used by therapists to assess children. There is limited information on how sensory profiles differ between very preterm (VPT) children and term controls, or on the predictors of sensory profiles in VPT children. Aims: The aim of this study was to examine sensory profiles of children born <. 30. weeks' gestation at 2. years and their environmental and biological influences. Study design: Cohort study. Subjects: 253 VPT children born <. 30. weeks' gestation and 65 term-born controls (>. 36. weeks' gestation). Outcome measures: Sensory profiles were examined with the Infant/Toddler Sensory Profile Questionnaire, which measures the child's responsiveness in four sensory quadrants and in five sensory processing sections. Standardised z scores for the VPT sample were compared with the controls, and predictors of VPT infant sensory profiles were determined. Results: VPT children had scores consistent with stronger patterns across all four sensory quadrants compared with controls, indicating a stronger interaction between neurological thresholds to elicit a response and self-regulation strategies. In addition they also exhibited more of the behaviours in all sensory processing sections compared with controls. Male sex, higher social risk, increasing length of stay, and moderate to severe white matter abnormality on MRI at term-equivalent age were associated with stronger sensory profile patterns in some quadrants, and more behaviours in some sensory processing sections. Conclusions: Sensory profiles differed between VPT children and term-born controls, with stronger sensory profile patterns associated with male sex, higher social risk, longer hospital stay, and moderate to severe white matter abnormality. © 2013 Elsevier Ltd.